Interaction between severe chronic kidney disease and acute kidney injury in predicting mortality after transcatheter aortic valve implantation: Insights from the Italian Clinical Service Project. Issue 7 (9th July 2020) - Adamo, Marianna; Provini, Martino; Fiorina, Claudia; Giannini, Cristina; Angelillis, Marco; Testa, Luca; Barbanti, Marco; Merlanti, Bruno; Poli, Arnaldo; Ferrara, Erica; Latib, Azeem; Reimers, Bernhard; et al.
Abstract: Aims: We aim at exploring whether severe chronic kidney disease (CKD) may modify the impact of acute kidney injury (AKI) post‐transcatheter aortic valve implantation (TAVI) on early, mid, and long‐term mortality. Methods and results: The analysis included 2, 733 TAVI patients from the Italian Clinical Service Project. The population was stratified in four groups according to the presence of baseline severe CKD and postprocedural AKI. All‐cause mortality was the primary end point. Postprocedural AKI is associated with an increased risk of early and mid‐term mortality after TAVI regardless of baseline severe CKD. Preprocedural severe CKD is associated with an increased risk of long‐term mortality after TAVI regardless of postprocedural AKI. No interaction between preprocedural severe CKD and postprocedural AKI was observed in predicting mortality at both 30‐day (CKD: hazard ratio [HR] = 2.65, 95% confidence interval [CI] = 1.15–6.12; no‐CKD: HR = 3.83, 95% CI = 2.23–6.58; P int = .129) and 1‐year (CKD: HR = 2.29, 95% CI = 1.37–3.82; no‐CKD: HR = 2.47, 95% CI = 1.75–3.49; P int = .386). Preprocedural severe CKD is an independent predictor of postprocedural AKI (HR = 2.17, 95% CI = 1.56–3.03; p < .001) as well as general anesthesia and access alternative to femoral. Among no‐AKI patients, those with severe CKD at admission underwent kidney function recovery after TAVI (serum creatinine at baseline 2.24 ± 1.57 mg/dL and at 48‐hr 1.80 ± 1.17 mg/dL; p = .003). Conclusions: Preprocedural severe CKD did not modify the impact of postprocedural AKI in predicting early and mid‐term mortality after TAVI. Closely monitoring of serum creatinine and strategies to prevent AKI post‐TAVI are needed also in patients without severe CKD at admission.